The history of the modern world : from 1900 to the present day - Burrows, Terry , 1955- (Carlton, 2012)
This is a comprehensive illustrated history of the world, from 1900 to the present day. The modern era, since the start of the twentieth century, is unique in human history for having been chronicled not just in words, as in previous generations, but also in visual detail, captured in photographs. The greatest images of this era are combined in The History of the Modern World, with authoritative text to document our times with immediacy and clarity. Every major event that has had a place in moulding our lives is chronicled - the death of a great queen, Victoria, at the beginning of the twentieth century and the tragic demise of a beloved princess, Diana, at its end; the civil unrest in the Balkans that led to the Great War and had grave, far-reaching consequences for Yugoslavia; the destruction in the 1900s of the old Imperial order that gave bloody birth to revolutions and civil wars and spawned the reigns of brutal dictators in Germany, Spain, Italy and Russia; the birth of the twenty-first century, with new millennium celebrations around the globe; the attack on the World Trade Center in New York; the catastrophic tsunami disaster in south Asia at the end of 2004; the trial and execution of Saddam Hussein at the end of 2006; the capture of a Royal Navy crew, allegedly in Iraqi waters, in 2007; and the election of US president Barack Obama in 2008. It also includes: the sudden death of Michael Jackson in 2009; the catastrophic Haiti earthquake in 2012; the pageantry of Britain's royal wedding in 2011; the sinking of the Costa Concordia in 2012; the technological, scientific and medical advances that have transformed every aspect of our lives; and the people - politicians, scientists, movie stars, icons and writers - who have shaped the way we think, feel and live. In unprecedented and graphic detail, The History of the Modern World is a concise and authoritative overview of this remarkable age: a time of war, peace, prosperity and progress